Amelia Bedelia and the surprise shower - Parish, Peggy; Thomas, Barbara Siebel ([New York] : HarperCollins, 1995)
Amelia Bedelia and her cousin, helping to prepare a surprise shower, make some arrangements that are not quite what the guests expected.
"Grades 1-3"--Cover.
"Level 2"--Cover.
Horn Book
School Library Journal
2.3
K-3
Keywords: Amelia-Bedelia (Fictitious character) -- Fiction; Humorous stories; Parties -- Fiction; Amelia-Bedelia (Fictional character) -- Fiction; Humorous fiction; Parties -- Fiction; Readers (Elementary).